2015
DOI: 10.1080/15592324.2015.1019983
|View full text |Cite
|
Sign up to set email alerts
|

Importance of phosphoinositide-dependent signaling pathways in the control of gene expression in resting cells and in response to phytohormones

Abstract: "Phosphoinositide" refers to phosphorylated forms of phosphatidylinositol, including phosphatidylinositol-4-phosphate and phosphatidylinositol-4,5-bisphosphate. Both of these molecules could be in vivo substrates of plant phospholipase C. These phosphoinositides can also be biologically active "per se," by directly binding to proteins and thus altering their location and/or activity. The use of pharmacological agents in Arabidopsis suspension cells allowed us to identify genes whose expression was positively o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…PI‐4Kβ1 (homolog of Potri.007G109000) is believed to affect SA (Janda et al ., 2014; Šašek et al ., 2014) via biosynthesis of phosphoinositides, which function as cofactors for enzymes involved in membranes and vesicles responsible in part for signaling molecule transport (Mayinger, 2012; Starodubtseva et al ., 2022). In addition to regulating levels of SA itself, phosphoinositides may regulate the action of downstream SA‐signaling genes, which are highly represented among targets of the phosphoinositide‐dependent phospholipase C (Kalachova et al ., 2015). Double loss‐of‐function mutants of PI‐4Kβ1 and the related PI‐4Kβ2 ( pi‐4kβ1, 2 ) show phenotypes including overaccumulation of SA (Janda et al ., 2014; Šašek et al ., 2014) and insensitivity to exogenous auxin (Starodubtseva et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…PI‐4Kβ1 (homolog of Potri.007G109000) is believed to affect SA (Janda et al ., 2014; Šašek et al ., 2014) via biosynthesis of phosphoinositides, which function as cofactors for enzymes involved in membranes and vesicles responsible in part for signaling molecule transport (Mayinger, 2012; Starodubtseva et al ., 2022). In addition to regulating levels of SA itself, phosphoinositides may regulate the action of downstream SA‐signaling genes, which are highly represented among targets of the phosphoinositide‐dependent phospholipase C (Kalachova et al ., 2015). Double loss‐of‐function mutants of PI‐4Kβ1 and the related PI‐4Kβ2 ( pi‐4kβ1, 2 ) show phenotypes including overaccumulation of SA (Janda et al ., 2014; Šašek et al ., 2014) and insensitivity to exogenous auxin (Starodubtseva et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there was a positive association between the genes regulated by basal DGK5 and the immune response as genes repressed in the dgk5.1 mutant versus WT were mostly involved in stress responses, including biotic stresses ( Supplemental Figure S13 ). Using a pharmacological approach, we had previously shown that DGK controlled the basal expression of a set of genes in Arabidopsis suspension cells ( Djafi et al, 2013 ; Ruelland et al, 2014 ; Kalachova et al, 2015 ). The data presented in this current work confirmed the importance of the PI-PLC/DGK pathway in the maintenance of basal gene expression and pointed out that a basal DGK5 activity is required for the positive expression of a basal immune response.…”
Section: Discussionmentioning
confidence: 99%
“…A secondary outcome of PA production via the PI-PLC/DGK pathway is the decrease of phosphoinositide levels. Phosphoinositides are involved in maintaining the transcriptome of resting cells and modulating the transcriptome in response to phytohormones ( Kalachova et al, 2015 ). Indeed, the majority of genes commonly regulated by ABA and SA show phosphoinositide-dependent expression ( Kalachova et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Under SA treatment, expression of MaPLC3 with SA-responsive elements in the promoter is suppressed, similarly in pepper cells SA can directly inhibit PI-PLC expression (Rodas-Junco et al, 2020). At the same time, it will inhibit the generation of other phospholipase signals production (Kalachova et al, 2015), but the expression of MaPLC2, MaPLC4 and MaPLC6 was signi cantly induced, probably due to the presence of adversityrelated action elements on their promoters. The results of the present study further suggested that PI-PLC genes play an important regulatory role in banana during growth and in response to stress, but the speci c regulatory mechanisms need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%